Taxonomic corrections to species of Rhyparochromidae (Hemiptera: Heteroptera) described by Carl Peter Thunberg - Kondorosy, Előd; Rédei, Dávid; Mejlon, Hans (Zootaxa, 2014)
Types of Rhyparochromidae (Hemiptera: Heteroptera: Lygaeoidea) species described by Carl Peter Thunberg, deposited in the Museum of Evolution (formerly Zoologiska Institut), Uppsala University, Uppsala, Sweden, were reexamined and the taxonomic and nomenclatural problems that existed among those species discussed and resolved as required. Lectotypes are designated for Cimex caffer Thunberg, 1784, Lygaeus ater Thunberg, 1822, Lygaeus biguttatus Thunberg, 1822, and Pendulinus guttatus Thunberg, 1825. The lectotype of Pendulinus (now Metochus) guttatus is designated as neotype of Pendulinus (now Metochus) uniguttatus Thunberg, 1822; as a result the former name becomes junior objective synonym of the latter. The following taxonomic changes are proposed: Lethaeus ater (Thunberg, 1822), new combination (from Lygaeus); Migdilybs biguttatus (Thunberg, 1822), new combination (from Lygaeus) = Migdilybs furcifer Hesse, 1925, new subjective synonym; Metochus uniguttatus (Thunberg, 1822) = Metochus bengalensis (Dallas, 1852), confirmed subjective synonym = Metochus yeh (Dohrn, 1860), confirmed subjective synonym; Raglius alboacuminatus (Goeze, 1778) = Cimex caffer Thunberg, 1874, confirmed subjective synonym. Lethaeus barberi Slater, 1964 does not belong to Lethaeus Dallas, 1852 but currently it cannot be placed with confidence in any existing genus.